O excesso do estado na criminalização do terrorismo por meio dos tipos penais abertos e a possibilidade de criminalização do direito de resistência - Marques, Fernando Tadeu (2022)
There is no precise date for the beginning of terrorism in the world, however, over the years and the evolution of laws, the international community, in the desire to curb the aforementioned criminal phenomenon, through its domestic legislation, started to to discipline and conceptualize terrorist acts and their respective sanctions. It just so happens that, precisely because of the complexity of the subject, the anti-terror norms, for the most part, started to conceptualize terrorism using generic and imprecise terms, using too much of the open penal types. In this context, this thesis aimed to analyze the excessive criminalization of terrorism through open criminal offenses and the possibility of deviating from the purpose of the rule to criminalize the right to resistance, notably, of social movements. In this scenario, a comparative study was carried out, in which the legislation of Brazil and other South American countries was observed, which proceed with the normative opening of the penal type to conceptualize terrorist acts, such as: Argentina, Paraguay, Uruguay and Venezuela. In fact, it was possible to verify that both in Brazil and in the aforementioned countries of South America, the laws that regulate terrorism use the so-called open criminal types, a fact that allows for a greater breadth of the rule, culminating in a greater extensive interpretation and analogue of the judge when applying the penal type that defines terrorism. Furthermore, it was possible to verify that these legislations were inserted in the legal system of the mentioned countries, in a scenario of repression of individual rights, such as in Brazil, in which the first legislation that mentioned terrorism was created within the scope of a military dictatorship, specifically , in the National Security Law. In these terms, in line with the totality of the above, it is evident that the current bills aimed at modifying the current anti-terror legislation can culminate in criminalizing social movements and, consequently, the very right to resistance